PENGARUH MODEL PEMBELAJARAN AKTIF DENGAN METODE QUESTION STUDENTS HAVE DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 7 DAN SMA NEGERI 8 PADANG - Jimi Ronald; Marwan Marwan (Jurnal Kajian Pendidikan Ekonomi, 2014)
This research was aimed at finding (1) the effect of using the ‘Question students Have’ method to the result of the learning between using the conventional method (2) the effect of the students’ learning motivation to the result of their learning, and (3) the interaction between the use of the Question students Have learning model and their motivation toward the students’ learning result in the subject of Economy. The research was a quasi-experiment whose population was grade XI IPS students of SMA negeri 7 Padang dan SMA Negeri 8 Padang. The sampling technique used was the purposive sampling. The experimental group was the grade XI IPS students of SMA Negeri 8 and the control group was Grade students of SMA Negeri 7 Padang. The data of the research consisted of two kinds: primary and secondary data. The data were analyzed by using a descriptive method and inductive analysis in the form of the two way ANOVA. The findings of the research were (1) The students taught with the Question Students Have scored significantly higher than those taught with the conventional method with the significance index (Sig) = 0.000 smaller than the value of 0.05 (sig. <α),(2) the students with high innovation scored significantly higher that those whose motivation were low with Sig : 0.000, smaller than the value of 0.05 (sig. <α) and (3) there was no interaction between the Question Students have and their motivation to the learning result with Sig= 0.301. This means the significance value was bigger then the alpha value 0.05 (Sig>a). Based on the findings, it is suggested that the teachers use this method or model in the teaching of Economy and always motivate the students. Keywords: Question students Have method, learning motivation, students learning result in the subject of Economy